The early prehistory of Scotland - Pollard, Tony; Morrison, Alex (Edinburgh University Press, 2010)
This book represents the first overview of current research into the early prehistory of northern Britain, and most particularly Scotland, since the publication of Lacaille's seminal Stone Age in Scotland in 1954. Many of the contributions included are papers presented at a conference marking the fortieth anniversary of Lacaille's publication, held at Glasgow University in October 1994. The aim of the conference to commemorate Lacaille's work, and to assess the advances made in the field of early prehistoric archaeology in Scotland. It was essential to bring together as many of those scholars working in the field as possible. The editors believe that this mixture has produced a work of considerable breadth, bringing together papers based on fieldwork and those demonstrating a more theoretical approach. Studies from outside Scotland are included but they maintain a northern focus. Much water has passed under the bridge since the appearance of Lacaille's book. A good many more sites have been discovered and excavated over the past forty years. Scientific techniques such as radiocarbon dating have been introduced and refined, and our understanding of prehistoric environmental conditions has advanced considerably. It is hoped that with the wide variety of papers presented, this volume goes some way towards giving shape and form to those who have for too long been the invisible people of Scottish prehistory.